Evaluating the Success of ZaZiBoNa, the Southern African Development Community Collaborative Medicines Registration Initiative - Sithole, Tariro (Ther Innov Regul Sci, 2020)
The Southern African Development Community (SADC) collaborative medicines registration initiative ZaZiBoNa is a successful regional work-sharing initiative on the African continent. This paper reviews the history of the ZaZiBoNa initiative, reflects on what has been realized in six years of operation and what still needs to be achieved. Statistics for the work done by the initiative are available in the literature, but there has not been a critical review of the process, including an analysis of factors contributing to the success of the initiative and conversely those negatively affecting performance. To do this, publicly available literature and statistics, meeting records, terms of reference and unpublished documents belonging to the initiative were reviewed. The successes of the ZaZiBoNa initiative can be attributed to leadership commitment, a clear vision and governance structure providing direction, and a clear, documented operating model, processes and objectives defined from the onset of the initiative. Closure of the gaps that were identified and implementation of the recommendations that were made in this paper will further strengthen the initiative. Furthermore, other regional harmonization or work-sharing initiatives on the African continent and beyond can draw lessons from this review of the ZaZiBoNa initiative for improved efficiency and effectiveness.